Effect of 12 Weeks Vitamin D Supplementation (Alphacalcidol) on Blood Pressure in Elderly Women Patients - Achmad Zaki; Nida Nabila; M. Djauhari Widjajakusumah; Witri Ardini; Mery Nitalia (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2021)
Background : Cardiovascular disease have overtaken communicable disease for being the main killer worldwide. Hypertension or high blood pressure is one of the risk factors. Elderly women statistically have a high prevalence of hypertension. Vitamin D is known to affect blood pressure and many studies showed the association between vitamin D and blood pressure with varying result. This study aim to evaluate the effect of vitamin D supplementation (alphacalcidol) for 12 weeks and change in blood pressure of elderly women patients in community health service clinic (KPKM) Medical Faculty Syarif Hidayatullah State Islamic University of Jakarta (FK UIN Jakarta), with pre and hypertension grade 1 patients in majority. Methods : Analytical pre-post study design was conducted as a part of an RCT (Randomized Controlled Trial) studies with 106 participants of elderly women (45 intervention group, 61 control group).Results : Vitamin D deficiency in the intervention group significantly decreased post-supplementation from 22.2% to 8.9%. Subgroup analysis showed the decrease in blood pressure is greater in the subgroup middle-age elderly than young-age elderly category. Even though there was a significant change in the diastolic blood pressure in the subgroup of middle-age elderly post supplementation (p=0.03), Mann-Whitney statistical analysis showed that 12 weeks vitamin D supplementation (alphacalcidol) did not significantly effect the pre and post systolic nor diastolic blood pressure (p>0,05). Conclusion : The study did not found significant effect of 12 weeks Vitamin D (alphacalcidol) supplementation on blood pressure in elderly women patients.